Toxoplasmosis accelerates the progression of hereditary spastic paraplegia - James R. Alvin; Carlos J. Ramírez-Flores; Caitlin A. Mendina; Anjon Audhya; Laura J. Knoll; Molly M. Lettman (mSphere)
ABSTRACT The parasitic protozoa Toxoplasma gondii chronically infects the central nervous system of an estimated one-third of the human population. Infection is generally subclinical, but immunocompromised individuals can experience a variety of neurological symptoms. Meta-analyses of T. gondii seropositivity have suggested a correlation between T. gondii infection and neurologic disease. Although mechanistic studies on the relationship between T. gondii infection and neurologic disease have been attempted in mice, they are particularly susceptible to T. gondii, making them an effective model for investigating mechanisms of infection, but not ideal for examining the relationship between long-term chronic T. gondii infection and neurologic disease. Rats more closely mimic human T. gondii cyst levels after acute infection, but a lack of rat models for neurologic disease has limited studies on the interplay between T. gondii infection and neurologic disease progression. We have employed a previously characterized rat model of a complex form of hereditary spastic paraplegia (HSP), a class of neurodegenerative disorders that cause axonal degeneration and lower limb spasticity, in order to assess the effect of chronic T. gondii infection on neurodegenerative disease. We find that infected rats with hereditary spastic paraplegia exhibit significantly exacerbated behavioral and neuromorphological HSP symptoms compared with uninfected HSP mutant rats, with little correlative effect in infected versus uninfected control animals. We further find that all infected rats, regardless of genotype, exhibit a robust immune response to T. gondii infection, presenting with parasite levels below the limit of detection of multiple assays of parasitemia and exhibiting no detectable increase in neuroinflammation 7 weeks post-infection. These results suggest that chronic undetected T. gondii infection may exacerbate neurodegenerative disease even in immunocompetent individuals and may contribute to neurodegenerative disease heterogeneity.IMPORTANCEThe long-term consequences of previous acute infections are poorly understood but are becoming increasingly appreciated, particularly in the era of long COVID. Altered progression of other diseases later in life may be among the long-term consequences of previous infections. Here, we investigate the relationship between previous infections with the parasite Toxoplasma gondii, which infects ~30% of the global population, and neurodegenerative disease using a rat model of hereditary spastic paraplegia (HSP). We find that previous infections with T. gondii accelerate motor dysfunction in HSP rats, despite robust clearance of the parasite by infected rats. Our results suggest that previously cleared infections may alter the progression of other diseases later in life and contribute to neurodegenerative disease heterogeneity.